Pediatric Myopia Progression During the COVID-19 Pandemic Home Quarantine and the Risk Factors: A Systematic Review and Meta-Analysis - Yang, Ze; Wang, Xiang; Zhang, Shiyi; Ye, Haiyong; Chen, Yuanqing; Xia, Yongliang (Frontiers in Public Health, 2022)
Background The COVID-19 pandemic has made many countries adopt restrictive measures like home quarantine. Children were required to study at home, which made parents worried about the rapid myopic progression of their children. To compare myopia progression during the COVID-19 pandemic home quarantine with the time before it and risk factors of myopia progression, we conducted this study. Methods We searched PubMed, Embase, the Cochrane Library, and Web of Science to find literature from December 2019 to March 2022 related to COVID-19 pandemic home quarantine and children's myopia progression. Outcomes of myopia progression included axial length and spherical equivalent refraction. Factors of digital screen device time and outdoor activity time were analyzed. Results Ten studies were included in this meta-analysis. Compared to the same period before the COVID-19 pandemic, spherical equivalent refraction decreased (OR = −0.27; 95% CI = [−0.33, −0.21]; Z = 8.42; P < 0.00001). However, the subgroup analysis showed that there were no significant differences in spherical equivalent refraction between the two groups in higher-grade school-aged children (grades 4 and above, 11 to 18 years old) (OR = 0.01; 95% CI = [−0.05, 0.07]; Z =0.4; P = 0.69). The outcome of axial length showed no significant difference (OR = 0.06; 95% CI = [−0.31, 0.44]; Z = 0.34; P = 0.74). As for risk factors, the forest plots showed that digital screen device time (OR = 4.56; 95% CI = [4.45, 4.66]; Z = 85.57; P < 0.00001) and outdoor activity time (OR = −1.82; 95% CI = [−2.87, −0.76]; Z = 3.37; P = 0.0008) were risk factors of myopia progression. Conclusion Compared with the time before the COVID-19 pandemic, myopia progression in children during COVID-19 pandemic home quarantine was accelerated, especially in younger children. Increased digital screen device and decreased outdoor activity times were risk factors. When home quarantine eases, more time on outdoor activities and less time on digital screen devices are needed for children. Systematic Review Registration https://www.crd.york.ac.uk/prospero/logout.php.